An annotated catalog of types of Neotropical Pierinae (Lepidoptera: Pieridae) in the collection of the National Museum of Natural History, Smithsonian Institution, Washington DC - Abadjiev, Stanislav P. (Zootaxa, 2005)
A catalog of the type material of 59 taxa of Neotropical Pierinae housed in the National Museum of Natural History, Smithsonian Institution, Washington, DC, is presented. Each entry includes the species-group name, the original combination quoted from the original publication, the type locality, the type specimens with their labels, and notes about current taxonomic status. One new synonym has been established, Euterpe dysoni Doubleday, 1847 = Leodonta marginata Schaus, 1902. Lectotypes are designated for 5 species group taxa: Archonias intermedia Schaus, 1913, Hesperocharis jaliscana Schaus, 1898, H. paranensis Schaus, 1898, Pieris sublineata Schaus, 1902, and P. limona Schaus, 1913.